Impact of Delay Time before Annealing MAI-PbI2-DMSO Intermediate Phase on Perovskite Film Quality and Photo-Physical Properties - Yujun Yao; Xiaoping Zou; Jin Cheng; Dan Chen; Chuangchuang Chang; Tao Ling; Haiyan Ren (Crystals, 2019)
High-performance perovskite solar cells are strongly dependent on the quality of the perovskite layer. Two-step sequential deposition of CH3NH3PbI3 (MAPbI3) films is widely used to fabricate perovskite solar cells and many factors influence the quality of perovskite films, such as the delay time before annealing the MAI-PbI2-DMSO intermediate phase, which would impact the morphology and photo-physical properties of perovskite thin films. Here, the experimental research indicates that the impact of the delay time before annealing the MAI-PbI2-DMSO intermediate phase on the quality, crystallinity, and photo-physical properties of perovskite film is crucial. During the delay process, the delay time before annealing the MAI-PbI2-DMSO intermediate phase plays an important role in the nucleation process of perovskite grains inside the intermediate phase. With the extension of the delay time before annealing, the quality of the perovskite film deteriorates, thus the photo-physical properties change. We found that after the localized liquid–liquid diffusion of MAI and PbI2, with the extension of the delay time before annealing the MAI-PbI2-DMSO intermediate phase, the nucleation number of the perovskite grains increases and the grain size becomes smaller. Therefore, with the extension of the delay time before annealing, the device performance deteriorates.